Tunnel dryer and pneumatic dryer performance evaluation to improve smallscale cassava processing in Tanzania - Precoppe, M.; Chapuis, Arnaud; Müller, J.; Abass, A. (Wiley, 2017)
In sub‐Saharan Africa, cassava is grown by smallholder farmers and is the principal source of calories for the local population. However, the short shelf life of cassava associated with poor infrastructure in the region results in significant postharvest losses. The expansion of small‐scale cassava processing could reduce these losses, but the availability of drying equipment suitable for use in such operations is limited. The objective of this research was to contribute to the development of cassava dryers suitable for use by smallholder farmers. A tunnel dryer and a pneumatic dryer being operated in Tanzania were evaluated using mass and energy balance analysis. It was found that the energy efficiency of the tunnel dryer was 29% and of the pneumatic dryer 46%. For the tunnel dryer, most of the heat losses were through unsaturated exhaust air, while for the pneumatic dryer, most losses were through radiation and convection.In this study, a tunnel dryer and a pneumatic dryer suitable for use by smallholder farmers were evaluated during processing centers' usual cassava drying operations. The sources and extent of heat losses were identified, and then guidelines developed on how to reduce such losses. For both dryer types, improvements to the thermal insulation used could reduce heat losses to the ambient. For the tunnel dryer, decreasing the air mass flow rate by 57% would help to minimize exhaust heat losses without producing condensation inside the unit. For the pneumatic dryer, air mass flow rate could be reduced by 9%, improving energy performance without having a negative impact on the pneumatic conveying of the product. Those two modifications would be easy to implement and represent a significant contribution to the development of small‐scale cassava drying technology.